3D numerical simulation of heat and mass transfer of fin-and-tube heat exchanger under dehumidifying conditions. (December 2018) - Li, Mingjie; Zhou, Wenjing; Wei, Jinjia; Tao, Wenquan
Highlights: Relative humidity has little effect on the temperature distribution of the fin. No condensation occurs near the inlet area. The maximum condensation mass flux is detected in the second row of pipe. Relative humidity has little influence on the sensible heat transfer rate. But manifests profound effects on the latent and total heat transfer rate. Abstract: The heat and mass transfer of a five-row fin-and-tube heat exchanger under dehumidifying conditions is numerically studied in this paper, and the distributions of vapor condensation mass rate for both fin and tube surfaces are obtained. The influences of vapor mass percent of humid air and inlet velocity on heat and mass transfer are investigated. Numerical results reveal that relative humidity has little effect on the temperature distribution of the fin under humid conditions. It is also noticed that no condensation occurs near the inlet area, and the maximum condensation mass flux is detected in the second row of pipe; this phenomenon is more obvious at higher inlet velocities. Relative humidity has little influence on the sensible heat transfer rate; however, it manifests profound effects on the latent heat transfer rate and total heat transfer rate. The dimensionless heat and mass transfer factors are also obtained from the numerical study and compared with the correlations in literature.